2011
DOI: 10.1136/bmjopen-2011-000318
|View full text |Cite
|
Sign up to set email alerts
|

Exploring differences in patient mix in a cohort of GP trainees and their trainers

Abstract: BackgroundDuring specialty training for general practice, trainees acquire the required competencies through work-based learning. Previous small-scale and older studies suggest that the patient mix of general practitioner (GP) trainees differs from that of their trainers: trainees are exposed to more minor illnesses, and fewer chronic diseases and severe conditions, which may influence the development of their competency.Research questionWhat are the differences in the patient mix between trainees and trainers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 23 publications
1
28
2
Order By: Relevance
“…One thousand, one hundred and forty-seven Read code descriptors existed for the presenting problems of the 2086 patients at their index events. Nineteen per cent (n = 213) of these were listed by de Jong et al 96 in their classification of acute or minor problems. The largest grouping was the minor/symptoms category ( Table 18).…”
Section: Case Studies: Evidence From the Consultation Records And Linmentioning
confidence: 99%
See 1 more Smart Citation
“…One thousand, one hundred and forty-seven Read code descriptors existed for the presenting problems of the 2086 patients at their index events. Nineteen per cent (n = 213) of these were listed by de Jong et al 96 in their classification of acute or minor problems. The largest grouping was the minor/symptoms category ( Table 18).…”
Section: Case Studies: Evidence From the Consultation Records And Linmentioning
confidence: 99%
“…A categorisation of the presenting problems in the index consultation was also assigned to each patient record in order to examine the case mix of the consulting patients. This classification of acute, chronic, minor/symptoms, prevention and processes was an adaptation of that used by de Jong et al, 96 developed by the research team in which the GP in the research team (SdeL) made the final decisions on categorisation and assignment. The method of assignment of a condition category to each patient is presented in Appendix 6.…”
Section: The Datamentioning
confidence: 99%
“…13 Current Australian guidelines for chlamydia screening in general practice recommend annual testing of all sexually active people aged 15-29 and patients with a recent change in partner or reporting inconsistent condom use. 14 A study of Australian general practitioners (GPs) found that chlamydia testing was occurring in 0.32% of patient encounters overall; however, in an age group most relevant to screening (age [15][16][17][18][19][20][21][22][23][24], tests were being performed in 1.32% of encounters. 15 The same study found that…”
mentioning
confidence: 99%
“…The Australian GP registrar cohort fits many of the predictors of greater likelihood of performing a chlamydia test: they are younger, more likely to be female, more likely to have graduated in Australia than overseas, 19 and are more likely to see patients who are new to the practice. 21 GP registrars have also been shown to see a higher proportion of younger patients 22 than their supervisors, and it is in younger patients that chlamydia screening is strongly advocated. It is, however, unknown if GP registrars actually perform regular chlamydia screening.…”
mentioning
confidence: 99%
See 1 more Smart Citation